ACTIVE TECTONIC STUDY IN NORTH BORNEO BASED ON AIRBORNE GRAVITY DATA - BRAMANTO - NIM : 22314301, BRIAN
Indonesia is a highly acitive seismicity region, indicated by more than 14,000 earthquake events with M>5 from 1897 to 2009. Those earthquakes were caused by IndonesiaÃ‚Â’s geographic position between four major tectonic plates and nine minor plates, however, there is a relatively low seismicity activity place in Indonesia, which is Borneo Island. After all, at 20 December 2015, there was an earthquake with magnitude up to M 6.1 occured in Tarakan, North Borneo with a depth of 14 kilometers. Gravity is one method in geophysics that can be used to identify geological structure with a wide area of interest. As technology develops, gravity measurement can be made using airborne, commonly referred as airborne gravity. This study aims to identive the active tectonics in the North Borneo region by appllying various method of gravity processing steps to enhance the gravity anomalies. To support the interpretation, combined data such as geological maps, tectonic deformation by GNSS data, earthquake distribution and earthquake focal mechanism. In general, there is accumulation energy zone that is indicated as the caused of earthquake events in Tarakan. By applying, derivative analysis on Bouguer anomaly, there is a indication of lateral continuity. The use of airborne gravity data provides a subsurface geological formation up to 20 kilometers depth. The focal mechanism of Tarakan earthquake in the end of 2015 is a West-East sinistral shear fault.